nugrohorisky25@gmail.com - Dwi Risky Nugroho; Roza Yulida; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aims of this study are to: (1) Describe the institutional of plantation extension in RokanHilir; (2) analyze the performance of plantation extension services in RokanHilir based onextensionworkers and farmers perception. This study was conducted in RokanHilir, the reason for taking this research is because RokanHilir is one of the regency that do not have a special institution to deal with extension activities. The method used to determine the sample in this research was purposive sampling, census, and Yaname Taro formula. Descriptive analysis is used to answer the first question and Likert Scale's Summated Rating (SLR) analysis was used to answer the second aim.The results showed: (1); The field of extension is a field that is responsible for extension activities that have 8 plantationextension, themembers who work in plantation offices are not appropriate with their background , while for the program areas of extension is not running well.(2) the perception of the extension workersperformance extension is in high category as can be seen fromthe responsiveness, responsibility, accountability and quality of service. Meanwhile, according to farmers' perception, the extension workersperformance is in the low category that can be seen from indicators of responsiveness, responsibility, accountability and quality of service. Keywords:Institutional, performance,extension institution